The perception and reality of added value in management consulting interventions - Goldfield, Tim (2006)
This dissertation investigates the value of consulting interventions through the eyes of both clients and consultants, seeking to identify the true nature of client perceived value. The objective is to identify how consultants add value to their client's organisations, the key factors for achieving this value and how value is defined and measured by clients.